“We Live in the Ruins of Christendom”: Bioethics in a Post-Engelhardtian Age - Paganini, Claudia (Conatus - Journal of Philosophy, 2018)
Hugo Tristram Engelhardt Jr. is a philosopher and a physician who has devoted all his life and all his creative power to developing and promoting a Christian bioethics. At the same time, the American is a personality who polarizes and has received euphoric praise on the one hand and malicious criticism on the other.  This has already been the case during his lifetime and will presumably remain so even after his death, which we wish to commemorate here. In the following contribution I intend to investigate why Engelhardt provokes so different reactions in the scientific community, and I will try to bring closer together the two seemingly irreconcilable parties of Engelhardt admirers and Engelhardt critics. I will do this by focusing on the two most controversial aspects of his research, his critique of the status quo and his concept of an independent Christian bioethics.